Modeling the Impacts of Urbanization on Regional Climate Change: A Case Study in the Beijing-Tianjin-Tangshan Metropolitan Area. (21st November 2013) - Zhan, Jinyan; Huang, Juan; Zhao, Tao; Geng, Xiaoli; Xiong, Yihui
Abstract : China has experienced rapid urbanization since 1978, and the dramatic change in land cover is expected to have significant impacts on the climate change. Some models have been used to simulate the relationship between land use and land cover change and climate change; however, there is still no sufficient evidence for the impacts of urbanization on the regional climate. This study aims to identify the impact of urban land use change on regional temperature and precipitation in summer in the Beijing-Tianjin-Tangshan Metropolitan area during 2030–2040 based on the analysis of the simulation results of WRF model. Firstly, we analyzed the land use change and climate change during 1995–2005 in the study area. The impacts of future urbanization on regional climate change were then simulated. The results indicate that urbanization in this area has affected the regional climate and has the potential to increase temperature and precipitation in the summer of 2030–2040. These research results can offer decision-making support information related to future planning strategies in urban environments in consideration of regional climate change.